Motivasi dan Prospeknya dalam Meningkatkan Kinerja Organisasi : Tinjauan Literatur - Hendartho, Dony (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2024)
Abstact : The coal industry in Indonesia is one of the most promising sectors, with trillions of rupiah in revenue each year. However, the rapid growth of this industry is not proportional to the risks it generates. Many coal companies still do not pay attention to This study aimed to determine employee motivation problems on organization performance and its prospects. An effective employee motivation system can inspire employee morale, improve employee productivity, enhance product quality, and create cohesion in the organization. Theories and motivation strategies that encourage the workers to improve their job performance were analyzed. The study adopts secondary sources of data collection for an overall understanding of the subject matter. However, many existing problems have negative impacts on the effective implementation of employee motivation systems. It was argued that there are many ways to enhance the performance of employees in an organization, in this manner, managers ought to endeavor to move forward their proficient quality, make an organizational culture, apply broadened inspiration strategies, pay consideration to representative preparing and career administration, use a complete set of benefits services, implement effective communication channel, set up an evenhanded installment framework as well as construct a great execution assessment framework. ABSTRAK : Penelitian ini bertujuan untuk mengetahui masalah motivasi karyawan terhadap kinerja organisasi dan prospeknya. Sistem motivasi karyawan yang efektif dapat menginspirasi semangat kerja karyawan, meningkatkan produktivitas karyawan, meningkatkan kualitas produk, dan menciptakan kohesi dalam organisasi. Teori dan strategi motivasi yang mendorong para pekerja untuk meningkatkan kinerja mereka dianalisis. Penelitian ini mengadopsi sumber data sekunder untuk mendapatkan pemahaman yang menyeluruh tentang pokok bahasan. Namun, banyak masalah yang ada memiliki dampak negatif pada implementasi sistem motivasi karyawan yang efektif. Dikatakan bahwa ada banyak cara untuk meningkatkan kinerja karyawan dalam suatu organisasi, dengan cara ini, manajer harus berusaha untuk memajukan kualitas mahir mereka, membuat budaya organisasi, menerapkan strategi inspirasi yang diperluas, memperhatikan persiapan perwakilan dan administrasi karir, menggunakan satu set layanan tunjangan yang lengkap, mengimplementasikan saluran komunikasi yang efektif, membuat kerangka kerja cicilan yang adil serta membangun kerangka kerja penilaian eksekusi yang hebat.